Pendidikan Karakter Perspektif Pendidikan Islam - Rakhmawati, Rakhmawati (Al-Ulum, 2013)
This article discusses about educational character on Islamic education perspective. Character education stresses the importance of unity between knowledge, attitude, and behaviour of each person to be able to life and collaborate, on family, and surrounding social communities. The realization of character educationon Islam perspective need special attention from parents, teachers, and the societies in forming children character early, included cognitive aspect, affective aspect, and physic motoric aspect. A trial to bear Islam young generation who have good faith to Allah and good character, then Islamic education as a lesson in school should be reconstruct included its curriculum. Islam lesson curriculum should put in priority the plenary values of Islam in its implementing; therefore, the character education in Indonesia will exist.